The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acsmacrolett.8b00484
|View full text |Cite
|
Sign up to set email alerts
|

Local pH and Effective pK of a Polyelectrolyte Chain: Two Names for One Quantity?

Abstract: In recent experiments, the “local pH” near polyelectrolyte chains was determined from the shift in the effective acidity constant of fluorescent pH indicators attached to the macromolecules. This indirect determination raises the question if the analyzed quantity was indeed the “local pH” and what this term actually means. In this study, we combined experiments and simulations to demonstrate that the shift in ionization constant is slightly lower than the difference between the pH and the “local pH”. This offs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 20 publications
0
38
0
1
Order By: Relevance
“…Various weak polyelectrolyte systems have been simulated using the RxMC method 24,4448 or cpH method 25,4957 . In RxMC 40 , we simulate chemical reactions by inserting and deleting particles, or by changing their chemical identity, as prescribed by the stoichiometry of the simulated reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Various weak polyelectrolyte systems have been simulated using the RxMC method 24,4448 or cpH method 25,4957 . In RxMC 40 , we simulate chemical reactions by inserting and deleting particles, or by changing their chemical identity, as prescribed by the stoichiometry of the simulated reaction.…”
Section: Introductionmentioning
confidence: 99%
“…As well as their role in underwater adhesives and encapsulation [21,23,24]. Extensive studies on the effects of counterions in determining the assembly and stability of polyelectrolyte complexes have been performed by several groups [25,26,27,28,29,30,31,32,33], though these have largely ignored the role of solution acidity in determining the charge on these compounds, which is crucial for dense polyelectrolyte assemblies [28,34,35,36,37,38]. Importantly, it was recently shown that the pH could significantly alter the charging equilibrium, and indeed the underlying thermodynamics of the process, when acidity and salinity are explicitly accounted for [33].…”
Section: Introductionmentioning
confidence: 99%
“…This non-monotonic trend in pK a cannot be explained by the polymer composition alone and is a complex function of monomer distribution and polymer conformation. [46][47][48] Compared to the low pK a value of the cationic homopolymer (P9 had a pK a =5.9), the copolymers incorporating HEMA exhibited pK a values that were up to 1.4 pH units higher, highlighting the critical, but frequently overlooked impact of polymer composition on polycation protonation. In summary, parallelized approaches to synthesis and characterization generated synthetic vector libraries that encompass a wide range of chemical compositions, interfacial properties, and protonation equilibria.…”
Section: Parallel Synthesis and Characterization Of A Combinatoriallymentioning
confidence: 98%